DINAMIKA ISU KEBIJAKAN PENANGGULANGAN BENCANA ABRASI DI KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Teguh Wahyono; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The abrasion disaster in Rangsang Pesisir District has threatened and brought disaster detrimental impact on society, losses in the form of assets, places of worship and community income. in 2020 the length of abrasion reached 44.8 Km abrasion disaster management continues to be carried out but is still not optimal due to several factors, namely the government's slow response, none maintenance of mangrove forests, lack of legal umbrella, development tackling is uneven, coping policies are experiencing changes to create dynamics. The aim of this research is to find out the actors, the interests of the actors, the interactions of the actors and their backgrounds social actors in the dynamics of abrasion disaster management policy issues in Rangsang Pesisir District, Meranti Islands Regency. This type of research is a qualitative research using the method of collecting data through interview, observation and documentation. The type of data used is data primary and secondary data. The data analysis technique used is interactive Miles and Huberman which consists of 3 namely data collection, data reduction, and draw a conclusion. The results of this study are the actors involved in abrasion disaster management includes BPBD, Rangsang Pesisir Sub-District, Villages in Rangsang Pesisir District, Communities and NGOs, interaction of actors in handling of abrasion goes well this is because it has similarities of the elements of the social base of the actors. Keywords: Actors, Interests, Resources, and Social Base